Legal Reform in Indonesia’s Response to the Digital Manipulation Era: A Responsive Legal Theory Approach - Antony, Antony; Sandoval, Excel Brayen; Louis, John Elvin (TRUNOJOYO LAW REVIEW, 2026)
The rapid advancement of technology has brought Indonesia into the era of digital manipulation, giving rise to various new social problems. This situation reveals the weaknesses and unpreparedness of the national legal system in responding to such challenges. A modern legal framework is therefore required to effectively address the need for legal protection in the digital era. This research aims to analyze the capacity of Indonesia’s legal system in addressing challenges arising from digital manipulation and to explore the relevance of responsive law theory as a framework for reform. This study employs a normative juridical method with a descriptive specification. The approaches used include the statutory approach, which examines legislative frameworks, and the conceptual approach, which analyzes the relevance of legal theories to digital manipulation. The findings indicate that Indonesian law has not yet optimally addressed the impacts of the digital manipulation era, particularly due to weak regulations, limited responsiveness, and limited mechanisms for public protection. Responsive law theory is viewed as an appropriate framework for building a modern legal system, as it emphasizes legal reform, flexibility, justice grounded in the public interest, public participation, and openness and transparency. This research contributes to improving the effectiveness of Indonesian law in responding to the challenges of the digital manipulation era. Its implementation requires political commitment, regulatory harmonization, and active public engagement. This research recommends revising and harmonizing digital regulations, strengthening legal literacy and education, and institutionalizing legislative audits based on responsive law indicators. Future studies should empirically test responsive law in practice to ensure that Indonesia’s legal system remains adaptive to challenges posed by digital manipulation.